Performance evaluation of passive DMFC single cells - Bae, Byungchan; Kho, Beck Kyun; Lim, Tae-Hoon; Oh, In-Hwan; Hong, Seong-Ahn; Ha, Heung Yong (ELSEVIER, 2006)
Passive direct methanol fuel cells have been extensively investigated for the effects of methanol concentration, catalyst loading of electrodes, fuel and oxidant supply modes and long-term operation on their performance. Passive cells to which the reactants, methanol and air, are supplied by natural convection flow without the help of any external devices, have shown very different behavior compared with an actively supplied cell. The optimum methanol concentration and catalyst loading in a passive cell are much higher than those of an active cell. The highest single cell performance was 45 mW cm(-2) with a 5 M methanol feed at room temperature and ambient pressure. Forced air to a passive cell was found to have a negative effect on the performance. In addition, experiments have been conducted to find the parameters that affect the long-term operation of a passive cell. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: METHANOL FUEL-CELLS; CROSSOVER; FABRICATION; POWER